Meta-analysis of the effect of the pringle maneuver on long-term oncological outcomes following liver resection - Khajeh, Elias; Shafiei, Saeed; Ali-Hasan-Al-Saegh, Sadeq; Ramouz, Ali; Hammad, Ahmed; Ghamarnejad, Omid; Saeedi, Mohammed al; Rahbari, Nuh Nabi; Reißfelder, Christoph; Mehrabi, Arianeb; Probst, Pascal; Oweira, Hani (Scientific reports, 2021)
Hepatic pedicle clamping reduces intraoperative blood loss and the need for transfusion, but its long-term effect on survival and recurrence remains controversial. The aim of this meta-analysis was to evaluate the effect of the Pringle maneuver (PM) on long-term oncological outcomes in patients with primary or metastatic liver malignancies who underwent liver resection. Literature was searched in the Cochrane Central Register of Controlled Trials (CENTRAL), Medline (via PubMed), and Web of Science databases. Survival was measured as the survival rate or as a continuous endpoint. Pooled estimates were represented as odds ratios (ORs) using the Mantel-Haenszel test with a random-effects model. The literature search retrieved 435 studies. One RCT and 18 NRS, including 7480 patients who underwent liver resection with the PM (4309 cases) or without the PM (3171 cases) were included. The PM did not decrease the 1-year overall survival rate (OR 0.86; 95% CI 0.67-1.09; P = 0.22) or the 3- and 5-year overall survival rates. The PM did not decrease the 1-year recurrence-free survival rate (OR 1.06; 95% CI 0.75-1.50; P = 0.75) or the 3- and 5-year recurrence-free survival rates. There is no evidence that the Pringle maneuver has a negative effect on recurrence-free or overall survival rates.
Gesehen am 26.03.2021